Genomic Analysis Identifies New Loci Associated With Motor Complications in Parkinson's Disease - Ryu, Ho-Sung; Park, Kye Won; Choi, Nari; Kim, Jinhee; Park, Young-Min; Jo, Sungyang; Kim, Mi-Jung; Kim, Young Jin; Kim, Juyeon; Kim, Kiju; Koh, Seong-Beom; Chung, Sun Ju (Frontiers in Neurology, 2020)
Background: Parkinson’s disease (PD) is a common neurodegenerative disorder, characterized by a clinical symptomatology involving both motor and nonmotor symptoms. Motor complications associated with long-term dopaminergic treatment include motor fluctuations and levodopa-induced dyskinesia (LID), which may have a major impact on the quality of life. The clinical features and onset time of motor complications in the disease course are heterogeneous, and the etiology remains unknown. Objective: We aimed to identify genomic variants associated with the development of motor fluctuations and LID at 5 years after the onset of PD. Methods: Genomic data were obtained using Affymetrix Axiom KORV1.1 array, including an imputation genome-wide association study (GWAS) grid and other GWAS loci; functional variants of the nonsynonymous exome; pharmacogenetic variants; variants in genes involved in absorption, distribution, metabolism, and excretion of drugs; and expression quantitative trait loci in 741 patients with PD. Results: FAM129B single nucleotide polymorphism (SNP) rs10760490 was nominally associated with the occurrence of motor fluctuations at 5 years after the onset of PD (odds ratio [OR] = 2.9, 95% confidence interval [CI] = 1.8–4.8, P = 6.5 × 10−6). GALNT14 SNP rs144125291 was significantly associated with the occurrence of LID (OR = 5.5, 95% CI = 2.9–10.3, P = 7.88 ×10-9) and was still significant after Bonferroni correction. Several other genetic variants were associated with the occurrence of motor fluctuations or LID, but the associations were not significant after Bonferroni correction. Conclusion: This study identified new loci associated with the occurrence of motor fluctuations and LID at 5 years after the onset of PD. However, further studies are needed to confirm our findings.